2021
DOI: 10.3390/biology10080790
|View full text |Cite
|
Sign up to set email alerts
|

agReg-SNPdb: A Database of Regulatory SNPs for Agricultural Animal Species

Abstract: Transcription factors (TFs) govern transcriptional gene regulation by specifically binding to short DNA motifs, known as transcription factor binding sites (TFBSs), in regulatory regions, such as promoters. Today, it is well known that single nucleotide polymorphisms (SNPs) in TFBSs can dramatically affect the level of gene expression, since they can cause a change in the binding affinity of TFs. Such SNPs, referred to as regulatory SNPs (rSNPs), have gained attention in the life sciences due to their causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Numerous studies have shown that SNP variation in coding regions, which affects the sequence of amino acids or the folding of peptide chains by changing codons, can alter certain phenotypic traits of organisms [ 38 – 40 ]. However, the effect of regulatory regions on animal phenotypes may be underestimated, and a growing number of studies have found the effects of regulatory regions on phenotypes [ 41 ]. In recent studies, regulatory regions have also been found to influence individual phenotypes by regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that SNP variation in coding regions, which affects the sequence of amino acids or the folding of peptide chains by changing codons, can alter certain phenotypic traits of organisms [ 38 – 40 ]. However, the effect of regulatory regions on animal phenotypes may be underestimated, and a growing number of studies have found the effects of regulatory regions on phenotypes [ 41 ]. In recent studies, regulatory regions have also been found to influence individual phenotypes by regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that SNP variation in coding regions, which affects the sequence of amino acids or the folding of peptide chains by changing codons, can alter certain phenotypic traits of organisms [38][39][40]. However, the effect of regulatory regions on animal phenotypes may be underestimated, and a growing number of studies have found the effects of regulatory regions on phenotypes [41]. In recent studies, regulatory regions have also been found to in uence individual phenotypes by regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have established a pipeline for the detection of rSNPs [6], which requires as input for each species a SNP catalog (as GVF file [26,27]), a reference genome (as fasta file), and gene annotations (as GFF3 file [28]). For all species except for rapeseed, the input data were downloaded from Ensembl Plants [23], with genome assemblies listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the search for causality of disease-or trait-associated SNPs, one often encounters regulatory SNPs (rSNPs) that influence the amount of genetic material, and hence play a crucial role in the expression of a phenotype. Compared to SNPs in the exonic regions, predicting the consequences of SNPs in the promoter regions is not as straightforward [3,[6][7][8]. Such consequences could be the disruption or creation of one or more transcription factor binding sites (TFBSs), which can have a major impact on the level of gene transcription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation